Economic Analysis of Agricultural Enterprises in Çanakkale - Burak Kocaköse; Duygu Aktürk (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to make economic analysis of the production period of 2017-2018 and the results of the annual activity. The data of the research was created as primary and original questionnaires through face-to-face interviews. The sample volume was determined by stratified sampling method. The enterprises are classified according to land size as 1-50, 51-100, 101- +. The questionnaire numbers were distributed proportionally to the producer. The average land size of the enterprises is 125,32 decare in the city. Gross production value (GSÜD) was found to be 191.766.73 TL, gross product (GSH) was 197.041.98 TL, gross profit was 756.73 TL/ha, pure product was 412.23 TL/ha and annual value was 367.77 TL/ha. When the production examined was examined, it was concluded that the history of the analysis in the third groups was told. In addition, economic profitability, financial profitability and financial profitability were reported as 2.57%, 3.27% and 26.22%, respectively.